The Effect Of Giving Pegagan (Centella Asiatica) Ethanol Extract On Incised Wound Healing In White Rats (Rattus Norvegicus) - Novida Ariani; Umi Kalsum; Adhinda Resta Camelia (Sean Institute, 2023)
This study aims to determine the effect of giving Centella asiatica on incised wound healing through the treatment of Centella asiatica on white rats (Rattus norvegicus). This study uses Experimental method in the form of a post-test only group design to determine the effect of Centella asiatica ethanol extract on the healing time of incised wound in white rats (Rattus norvogicus). The sample used in this study was 20 white rats divided into five treatment groups. Data analysis used quantitative analysis with helped of SPSS 29 software. The data test consisted of normality, homogeneity, and one way ANOVA test. The result showed 10% Povidone iodine, vaseline, 10% ointment of Centella asiatica ethanol extract, 15% ointment of Centella asiatica ethanol extract, and 25% ointment of Centella asiatica ethanol extract had the same effect on incised wound healing in white rats (Rattus norvogicus). Intervention with 10% Povidone iodine had average healing time of 12,75 days; intervention with 10% ointment of Centella asiatica ethanol extract had average healing time of 10 days; intervention with 15% ointment of Centella asiatica ethanol extract had average healing time of 8,75 days; and intervention with 25% ethanol extract Centella asiatica had average healing time of 12,75 days. The normaly test shows that the entire group has a significant value of p>0,05, so it says that the data is normally distributed. The homogeneity test shows an overall significance of p>0,05, so the data is nuanced and homogeneous. The ANOVA test showed a significance of p = 0,152, so the value of p >0,05, meant that there was so significant difference between groups. This study proved that the application of Centella asiatica ethanol extract ointment can be used as an alternative in the treatment of incised wound, such as post-section caesarean wound care.